What reason can be used to complete this proof?


m∠1=m∠3 because ∠1≅∠3.

m∠1+m∠2=m∠CXB and m∠2+m∠3=m∠AXD _________.

m∠1+m∠2=m∠AXD because you can substitute m∠1 for m∠3.

m∠CXB=m∠AXD by the transitive property of equality.

So, ∠AXD≅∠CXB.

Respuesta :

Answer:

Option (2)

Step-by-step explanation:

Given:

∠1 ≅ ∠3

To Prove:

∠AXD ≅ ∠CXB

Solution:

Given question is incomplete; find the complete question in the attachment.

            Statements                                                              Reasons

1). m∠1 ≅ m∠3 because m∠1 ≅ m∠3          1). Given

2). m∠1 + m∠2 = m∠CXB and                    

    m∠2 + m∠3 = m∠AXD                            2). Angle addition postulate

3). m∠1 + m∠2 = m∠AXD                             3). Because you can substitute

                                                                          m∠1 for m∠3

4). m∠CXB = m∠AXD                                   4).Transitive property of equality

5). ∠AXD ≅ ∠CXB

Therefore, Option (2) will be the correct option.

Ver imagen eudora